Cost–benefit analysis for optimal DG placement in distribution systems by using elephant herding optimization algorithm - C. Hari Prasad; K. Subbaramaiah; P. Sujatha (Renewables: Wind, Water, and Solar, 2019)
Abstract Distributed generations (DGs) are small generating plants which are connected to consumers in distribution systems to improve the voltage profile, stability improvement, reduction in power losses and economic benefits. The above benefits can be achieved by optimal placement of DGs. In this paper, a novel nature-inspired algorithm called elephant herding optimization algorithm is used to determine the optimal distributed generation size. It has been developed based on herding behaviour of elephant groups in nature. The proposed algorithm is tested on IEEE 15-, 33- and 69-bus test systems. The proposed algorithm with type III DG unit operating at 0.9 pf gives better results when compared with other methods in the literature.